The Density and Viability of Metarhizium anisopliae Conidia on Several Growth Media - Indriyanti, Dyah Rini; Bintari, Siti Harnina; Setiati, Ning; Alfiyan, Jamil Maulana Zahriyan (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Metarhizium anisopliae is a parasitic fungus on insects, and thus called entomopathogenic fungus. This fungus is used as a biological control agent for insect pests. Fungal propagation can be done using a variety of media. The purpose of this study was to analyze the growth of M. anisopliae on four types of media, with conidial density and viability as the growth parameters. This research was conducted at the Laboratory of Microbiology, Universitas Negeri Semarang. This study was an experimental research used a Completely Randomized Design (CRD) with one factor and four treatments: Control (PDA/Potato Dextrose Agar medium), Treatment I (ELSA/Extract Larvae Sucrose Agar medium), Treatment II (CWSA/Coconut Water Sucrose Agar medium), Treatment III (CWELSA/Coconut Water and Extract Larvae Sucrose Agar medium). The and results showed that there was an effect of growth media on the density and viability of M. anisopliae conidia. CWELSA media had the highest conidial density (2.91 x 108 cfu/mL) and viability (97.17%). CWSA media hadÂ 2.82 x 108 cfu/mL and 95.33%. PDA media had 2.25 x 108 cfu/mL and 92.83%. ELSA media had 1.64 x 108 cfu/mL and 90.83%. The high conidial density and viability of M. anisopliae is CWELSAÂ medium. This study is as an alternative growth medium to improve the quality of M. anisopliae propagation.